Collective Action and Climate Change Adaptation in Makassar - Anirwan Anirwan; Qamal Qamal (Journal of Government and Politics (JGOP), 2023)
Climate change is a problem that requires a variety of responses from individuals and institutions. Each entity can influence climate change policy and action, but as a complex matter, it is not surprising that there are deficiencies in climate change policy. This challenge highlights the need better to understand the selection of climate change adaptation programs. Therefore, this study aims to analyze how the collective action of various Makassar City Government institutions in the climate change adaptation program. This study uses a qualitative exploratory approach, with data collection through interviews and document review. The results of this study indicate that the collective action of the Makassar City Government can be assessed at the Climate Change Adaptation Working Group (Pokja-API), which consists of six institutions. It is just that the coordination between institutions that are members of the Working Group there is still a missing link between the programs that are the priorities of each institution.